Pengaruh Lingkungan Kerja, Motivasi Kerja, dan Kompensasi Terhadap Kinerja Karyawan pada Dealer Motor Astra Rem-bang 2 Kecamatan Rembang - Agista Dhea Abdiana; Anik Nurhidayati (Pusat Riset dan Inovasi Nasional, 2026)
Astra Rembang Motorcycle Dealer is a retail sales company engaged in the field of motorcycle sales and service (workshop) that specifically serves Astra Honda products. Astra Motorcycle Dealer is an official Honda dealer located at Jl. Dr. Wahidin No. 2B, Rembangan, Tasikagung, Rembang District, Rembang Regency. The Astra Rembang Motorcycle Dealer not only functions as a place to sell vehicles, but can also service motorcycles with all kinds of problems, from minor problems such as oil changes or even serious damage such as engine failure. Problems at the Astra Rembang 2 Motorcycle Dealer relate to the conditions of the employee's work environment. The performance of Astra Rembang 2 Motorcycle Dealer employees in Rembang District was analyzed for the influence of the work environment, work motivation and compensation. The approach used is quantitative. The sample was taken using a saturated sampling technique from a population of 35 employees. Analysis of data obtained through questionnaires, which measure work environment indicators, work motivation, compensation and employee performance, was carried out using multiple linear regression. It can be concluded that the work environment significantly improves the performance of Astra Rembang 2 Motorcycle Dealer employees, Rembang District. Work motivation has a positive and insignificant influence on the performance of employees at the Astra Rembang 2 Motorcycle Dealer, Rembang District, while employee performance is negatively and significantly influenced by compensation. Partially, as much as 46.9% of the variation in employee performance can be explained by these three variables. So, increasing these three variables will strengthen the performance of Astra Rembang 2 Motorcycle Dealer employees, Rembang District.